Infection control and prevention in burn victims: The role of nurses - Dorcas Ayomikun Ariyo; Olaolorunpo Olorunfemi (Wolters Kluwer Medknow Publications, 2024)
Burn injury is a major public health concern, with an estimated 180,000 deaths each year associated with burn-related infections. The majority of these occur in low- and middle-income countries, and almost two-thirds occur in the World Health Organization African and South-East Asia Regions. There is a risk of an escalation of burn injury site infections if nurses who are directly involved in burn care do not develop a mechanism to mitigate this risk in the coming years. Hence, this study aims at explaining what burn injuries are and how nurses can prevent the occurrence of infection among burn victims. This review analyzed published studies using keywords such as burn injury, infection in burn patients, and nurses' involvement in infection prevention and control (IPC) on search engines such as PubMed, Science Direct, and Google Scholar. The literature was retrieved and reviewed for eligibility to capture just the variables indicated in this seminar objective; the date range chosen in the literature search was from 2015 to 2023. The study found that many patients die from burn injuries as a result of exposure to infection and most nurses are not adequately informed about infection control. The study also found that nurses' responsibilities include proper hand hygiene, wound care, the use of personal protective equipment, antibiotic medication, cleaning the patient's surroundings, and preventing patient cross-contamination. Burn injuries pose a significant risk to patients, necessitating infection control and prevention. Therefore, nurses in burn units should be informed on IPC practices and also educate patients, families, and coworkers on their importance.